Vasculitis—What Do We Have to Know? A Review of Literature. (December 2018) - Shavit, Eran; Alavi, Afsaneh; Sibbald, R. Gary
Cutaneous and other vasculitides are specific inflammations of the blood vessel wall that can take place in any organ system of the body including the skin. Vasculitis has been traditionally divided according to the size of the vessel involved (small, medium, and large). Vasculitis is more of a reaction pattern rather than a specific disease entity. Therefore, the clinical presentation of vasculitis (most commonly palpable purpura on the lower extremities) dictates a thorough history, review of systems, and a meticulous physical examination. The diagnosis of vasculitis relies also on the histopathological and immunofluorescence studies. Wound care specialist may face with vasculitis-associated ulcers along with a spectrum of other cutaneous presentations associated with vasculitis. The focus of this article is to update the types, etiology, pathogenesis, and management options for cutaneous vasculitis.